PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS LEARNING CYCLE 5-E PADA POKOK BAHASAN KOLOID - Warlis, Erma; M. Noer, Asmadi; Susilawati, Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to develop Student Worksheets Based Learning Cycle 5-E on the Colloid which are valid based on the feasibility aspect of content, language, presentation and graphic. The type of the research is research and development (R and D) with reference to the development process of 4-D model. The object of this research is student worksheets based learning cycle 5-E. The instrument of data collection are validation sheets given to three validators and the result of data analysis was obtained by the validity of aspect of content, language, presentation and graphic are 90,28%, 90%, 91,67% and 91,67% with valid category. The students activities worksheets which validated by the validators tested to 20 students and get response result with percentage of 90,71% with positive category and student worksheet was also assessed by twochemistry teachersand get response result with percentage of 96,88% with positive category. Based on the data analysis, it can be concluded that student worksheets based learning cycle 5-E that produced is valid and can be used on Senior High School chemistry subject of colloid.Key Words: Colloid, Student Worksheet, Learning Cycle 5-E